Accounting Analysis of Crypto Assets and the Treatment of Current PSAK in Indonesia - Wibowo, Daryanto Hesti; Suwongso, Imanuel; Setiawan, Yusup; Jimmy, Ucok; Djumiyati, Dewi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the accounting treatment of crypto assets in Indonesia by examining the correctness of implementation of Indonesian Financial Accounting Standards (PSAK), as well as to evaluate whether the accounting conceptual framework responds to the dynamics of the digital economy. A systematic literature review approach is applied for this research, combining the analysis of national regulations—such as PSAK 238 on Intangible Assets and PSAK 202 on Inventory—with the international frameworks and policies, such as IFRS and FASB. The findings indicate that Indonesia does not have a specific PSAK that explicitly regulates digital assets. It causes the entities continue to rely on an analogy-based approach between PSAK 238 and PSAK 202, leading to variations in reporting treatment and affecting the comparability and relevance of financial information across companies. This study recommends the development of a specific PSAK regarding the digital assets that integrates the principles of relevance and faithful representation, as well as harmonization with IFRS, in order to ensure the consistency and comparability in financial reporting in the digital era.